Health Care Current Reviews 2019
DOI: 10.35248/2375-4273.19.07.238
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Pregnant Mothers towards Preventions of Iron Deficiency Anemia in Ethiopia: Institutional Based Cross Sectional Study

Abstract: Background: Globally 56 million (41.8%) of pregnant women had anemia. Low maternal risk perception, poor dietary practice and low adherence to iron tablets among pregnant women are major contributors for high burden of anaemia. Thus the level of maternal awareness and attitude towards dietary and other prevention practices of anaemia are not well established in the study area. Objectives: To assess the knowledge, attitude and practice of pregnant mother towards the prevention of iron deficiency anaemia in Ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
0
14
2
Order By: Relevance
“…Total of 128 mothers was interviewed with a mean age of 26.3 years and the majority (58.6%) having poor adherence to prevention practice of IDA. [24] Moreover, the findings from this study show that there was no significant relationship between awareness of anemia and its prevention among pregnant women in the study setting. This finding is similar to the report of Adznam et al [18] on knowledge, attitude, and practice levels regarding anemia among pregnant women in Putrajaya, in which respondent's knowledge had no significant relationship with the practice of prevention of malaria during pregnancy.…”
Section: Variables Never (%) Rarely (%) Sometimes (%) Often (%) Alwaymentioning
confidence: 56%
“…Total of 128 mothers was interviewed with a mean age of 26.3 years and the majority (58.6%) having poor adherence to prevention practice of IDA. [24] Moreover, the findings from this study show that there was no significant relationship between awareness of anemia and its prevention among pregnant women in the study setting. This finding is similar to the report of Adznam et al [18] on knowledge, attitude, and practice levels regarding anemia among pregnant women in Putrajaya, in which respondent's knowledge had no significant relationship with the practice of prevention of malaria during pregnancy.…”
Section: Variables Never (%) Rarely (%) Sometimes (%) Often (%) Alwaymentioning
confidence: 56%
“… 33 , 38 , 39 These findings are lower than the 66.9% of antenatal attendees in a general hospital in Lagos, Nigeria that drank tea in a study reported by Yesufu et al 40 ; the 75.3% of participants who took tea or coffee in a study reported by Wemakor 24 among pregnant women from Northern Ghana and the 46.9% who reportedly took coffee or tea immediately after their meals in a study reported by Oumer and Hussein. 41 The variations could be due to socio-economic, cultural and contextual differences. It is however an interesting conundrum that majority of the pregnant women in the current study did not know the foods that can improve or impede the absorption of iron in the body, although they consumed more vitamin C rich foods but limited the intake of tea and coffee.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of a problem may lead to its understanding and behavioral change, while attitude is a factor that can influence anemia intervention program. A study in Ethiopia by Oumer and Hussein 2019 reported good knowledge and attitude among their participants but poor adherence to prevention practice [19]. The report from Tanzania [14] revealed low knowledge and poor attitude among participants and a significant association of these with anemia.…”
Section: Discussionmentioning
confidence: 99%